Techniques and Instrumentation for Detection of Exoplanets X 2021
DOI: 10.1117/12.2594998
|View full text |Cite
|
Sign up to set email alerts
|

Planet matching and orbit determination in multi-planet systems for exoplanet direct imaging

Abstract: A key aspect of the search for Earth-like exoplanets with direct imaging is determining if the exoplanet is in the habitable zone. Future direct imaging mission concepts such as HabEx and LUVOIR require an efficient cadence of observations. Previous work shows that a minimum of three epochs, spanning more than half a period, can determine orbital parameters to 10% for a single, circular orbit. Multi-planet systems may require a different number and cadence of observations. We begin to address the multi-planet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Reference 14 showed that prior knowledge of the orbits of potentially Earth-like planets from precursor radial velocity observations can increase the speed at which a mission can spectrally characterize exoEarths. Reference 15 considered using orbit estimates of detected planets to adjust the cadence of observations for a given star.…”
Section: Introductionmentioning
confidence: 99%
“…Reference 14 showed that prior knowledge of the orbits of potentially Earth-like planets from precursor radial velocity observations can increase the speed at which a mission can spectrally characterize exoEarths. Reference 15 considered using orbit estimates of detected planets to adjust the cadence of observations for a given star.…”
Section: Introductionmentioning
confidence: 99%